Counselling Loss as a New Variable in the Education Production Function - Hornor, Tara; Westberry, Lee A. (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2023)
The purpose of this qualitative study was to investigate counselling loss as a new variable in the education production function as a result of the COVID-19 pandemic and the associated social and emotional impact on students. Study participants unanimously reported a sizable counselling loss and a 30 percent average decrease in time spent in direct counselling service provision during the COVID-19 pandemic; at the same time, students’ counselling needs increased. Participants identified three salient categories of impact from counselling loss associated with the pandemic, including emotional manifestations, social manifestations, and students’ growth and development-related opportunity loss.